2, 2′, 4, 4′-tetrabromodiphenyl ether induces thyroid toxicity by targeting BRAF-mediated MEK-ERK-NIS pathway in human thyroid follicular epithelial cells - Guangshan Xie; Jinping Lu; Jiayi Song; Jianqing Zhang (Ecotoxicology and Environmental Safety)
2, 2’, 4, 4’-tetrabromodiphenyl ether (BDE-47), one of the most abundant and toxic congeners of polybrominated diphenyl ethers (PBDEs), has been implicated in thyroid disorders, but its thyroid toxicity in human thyroid cells and underlying mechanisms remain unclear. Given the pivotal role of the V-Raf murine sarcoma viral oncogene homolog B (BRAF) and the downstream mitogen-activated protein kinase kinase (MEK)- signal-regulated kinase (ERK) pathway in cell proliferation, differentiation, cell cycle and thyroid functions, in this study, we constructed BRAF knockout (BRAF-KO) and overexpression (BRAF-OE) cell models using Nthy-ori 3-1 cells, to evaluate the effect of BDE-47 on human thyroid cells and explore the potential mechanisms. Our results showed that exposure to BDE-47 resulted in reduced cell viability, Gap 2 (G2)/mitosis (M) phase cell cycle arrest, enhanced cell migration, and decreased cell invasion. BRAF overexpression significantly exacerbated BDE-47-triggered cell cycle arrest and cell migration but alleviated its suppression of invasion, while BRAF knockout showed no significant effects, underscoring the crucial role of BRAF in BDE-47-induced cytotoxicity. Moreover, BRAF overexpression amplified BDE-47-triggered upregulation of phosphorylated MEK1/2 and ERK1/2 downregulation of sodium-iodide symporter (NIS), a well-known indicator of cellular iodine uptake. Molecular docking further indicated that BDE-47 likely activated the MEK-ERK- NIS signal cascade by directly binding to BRAF. This study demonstrated for the first time that BDE-47 led to reduced cell proliferation, cell cycle arrest, altered migration and invasion, and impaired iodine uptake through targeted activation of the BRAF-MEK-ERK signaling pathway. These findings elucidated a novel mechanism of BDE-47-induced thyroid toxicity, highlighting BRAF as a critical mediator for PBDEs-related thyroid dysfunction, offering insights for targeted interventions.